2014
DOI: 10.4161/sgtp.27539
|View full text |Cite
|
Sign up to set email alerts
|

Rho, nuclear actin, and actin-binding proteins in the regulation of transcription and gene expression

Abstract: Actin cytoskeleton is one of the main targets of Rho GTPases, which act as molecular switches on many signaling pathways. During the past decade, actin has emerged as an important regulator of gene expression. Nuclear actin plays a key role in transcription, chromatin remodeling, and pre-mRNA processing. In addition, the "status" of the actin cytoskeleton is used as a signaling intermediate by at least the MKL1-SRF and Hippo-pathways, which culminate in the transcriptional regulation of cytoskeletal and growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 149 publications
(195 reference statements)
1
67
0
4
Order By: Relevance
“…activation occurs independent of desmosome loss in the context of mTORC1 loss of function. ROCK itself has a well-described role in the regulation of gene transcription networks, and is a key effector of cellular mechanotransduction in this capacity (29). Thus, we hypothesized that decreased desmosomal gene expression in cKO cells could itself be due to increased cytoskeletal tension mediated by ROCK activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…activation occurs independent of desmosome loss in the context of mTORC1 loss of function. ROCK itself has a well-described role in the regulation of gene transcription networks, and is a key effector of cellular mechanotransduction in this capacity (29). Thus, we hypothesized that decreased desmosomal gene expression in cKO cells could itself be due to increased cytoskeletal tension mediated by ROCK activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the apparent lack of a proliferation defect in the RhebcKO model suggested the possibility of additional mechanisms contributing to the defective stratification seen in both models with mTORC1 loss of function. By K14 immunostaining, we noted that the basal-layer keratinocytes of the Rheb-cKO epidermis cytoskeletal contractility may exert complex effects on downstream gene expression through mechanotransduction, affecting the activity of multiple transcription factors (29). Despite this wealth of in vitro data, relatively little is known about the in vivo requirement of actomyosin contractility for desmosomal adhesion and epidermal barrier formation.…”
Section: Introductionmentioning
confidence: 99%
“…(27) Multiple recent studies have confirmed the effect of RhoA in either cytoplasmic or nuclear actin dynamics, which then modulate gene expression through chromatin remodeling complexes or the Hippo pathway. (42) Although the precise mechanisms by which AMBN affects individual gene expression remain to be discovered, the highly significant effect of AMBN on cytoskeletal dynamics via cell adhesion mechanisms opens the door to a plethora of signal cascades and epigenetic downstream effects through chromatin remodeling that may be affected by minute changes in local AMBN concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, in cultured cells the ratio of G-actin to F-actin is approximately 1:1. 47 RhoA activation causes increased actin polymerization and formation of stress fibers. The subsequent loss of free G-actin leads to the dissociation of the transcriptional co-activator megakaryoblastic leukemia 1 (MKL1) that normally binds G-actin monomers in the cytoplasm.…”
Section: Rhoa Regulates Transcription By Modifying the Status Of The mentioning
confidence: 99%